Dysregulated NAD(H) homeostasis associated with ciprofloxacin tolerance in Escherichia coli investigated on a single-cell level with the Peredox [NADH:NAD+] biosensor - Urbaniec, Joanna; Sanderson-Smith, Martina; McFadden, Johnjoe; Hai, Faisal I.; Hingley-Wilson, Suzanne M. (Frontiers in Microbiology, 2023)
Antibiotic persistence (subpopulation tolerance) occurs when a subpopulation of antibiotic sensitive cells survives prolonged exposure to a bactericidal concentration of an antibiotic, and is capable of regrowth once the antibiotic is removed. This phenomenon has been shown to contribute to prolonged treatment duration, infection recurrence, and accelerated development of genetic resistance. Currently, there are no biomarkers which would allow for segregation of these antibiotic-tolerant cells from the bulk population prior to antibiotic exposure, limiting research on this phenomenon to retrograde analyses. However, it has been previously shown that persisters often have a dysregulated intracellular redox homeostasis, warranting its investigation as a potential marker for antibiotic tolerance. Furthermore, it is currently unknown whether another antibiotic tolerant subpopulation - viable but non-culturable cells (VBNCs), are simply persisters with extreme lag phase, or are formed through separate pathways. VBNCs similarly to persisters remain viable following antibiotic exposure, however, are not capable of regrowth in standard conditions. In this article we employed an NADH:NAD+ biosensor (Peredox) to investigate NADH homeostasis of ciprofloxacin-tolerant E. coli cells on a single-cell level. [NADH:NAD+] was used as a proxy for measuring intracellular redox homeostasis and respiration rate. First, we demonstrated that ciprofloxacin exposure results in a high number of VBNCs, several orders of magnitude higher than persisters. However, we found no correlation in the frequencies of persister and VBNC subpopulations. Ciprofloxacin-tolerant cells (persisters & VBNCs) were actively undergoing respiration, although at a significantly lower rate on average when compared to the bulk population. We also noted significant heterogeneity on a single-cell level within the subpopulations, however we unable to segregate persisters from VBNCs based on these observations alone. Finally, we showed that in the highly-persistent strain of E. coli, E. coli HipQ, ciprofloxacin-tolerant cells have a significantly lower [NADH:NAD+] ratio than tolerant cells of its parental strain, providing further link between disturbed NADH homeostasis and antibiotic tolerance.